Inovasi Pelayanan Dinas Kearsipan dan Perpustakaan Kabupaten Cianjur di Masa Pandemi Covid-19 - Putri Nur Nabihatul Ghofilah (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
The presence of Covid-19, which is considered a global pandemic at this time has had a huge influence on various aspects of activities in human life, many activities have had to be stopped or postponed including library service activities. The existence of a work from home policy as a step to anticipate the transmission of the corona virus, causing library employees to work from home and carry out various activities online. So that the library cannot provide services to the community directly. Therefore, libraries need to create new innovations in order to provide services according to the information needs of the community in the midst of a pandemic. This study aims to determine the innovations that the Office of Archives and Libraries of Cianjur Regency have in providing services to the public or library users during the Covid-19 pandemic. The method used in this research is descriptive qualitative method. Data collection techniques used are literature study, observation, interviews, and documentation. While the data analysis used is data reduction, data presentation, and drawing conclusions. The results in this study indicate that due to the covid-19 pandemic, the library service system has changed. The various kinds of face-to-face services are limited and switched through digital services. To deal with the situation,The Office of Archives and Libraries of Cianjur Regency seeks to create new innovations in order to continue to provide sources of information to the public with recommend access to digital services in the form of the Ipusnas application and the CANDIL application. It is hoped that all libraries can continue to provide various kinds of innovations by implementing technology-based services. Keywords: Covid-19 Pandemic; Libraries; Innovation; Services